IoT for monitoring carbon monoxide (CO) emissions using wireless sensor networks in smart cities - Lakshmi Paruchuri, Vijaya; P. Rajesh, Dr (International Journal of Engineering and Technology, 2018)
A Smart city is characterized by the efficient use of information technology and industrial assets for financial improvement. Internet of Things (IoT) is an arrangement of embedded devices that communicates by using the internet and uniquely addressable with standard protocols. Application areas of Internet of things are smart cities, environmental protection, smart transportation, healthcare, agriculture and public security. Development of Smart cities leading to Pollution. Air Pollution is an environmental health concern for the public. Carbon Monoxide is a harmful gas to the human beings and also the leading cause of air pollution. So it is necessary to develop a mechanism for the detection of carbon monoxide molecules. This paper presents a survey on the methods of measuring the Carbon Monoxide emissions by using Wireless Sensor Networks. Availability of CO data from a monitoring program can be utilized for providing the awareness to the public about the air pollution.Â Â